Granting of Foundation Management Wage Rights and Dispute Resolution Mechanism Based on Law Number 28 of 2004 - Rotinsulu, Indriyawaty; Almoravid Dungga, Weny; Fazri Elfikri, Nurul (Cv. Kalimasada Group, 2025)
This study discusses in depth the legal provisions for the provision of remuneration to Foundation administrators in Indonesia and the related dispute resolution mechanisms, based on Law No. 28 of 2004 concerning Amendments to Law No. 16 of 2001 concerning Foundations. As a non-profit legal entity, a Foundation has unique characteristics that emphasize the principle of non-profit, where the use of the Foundation's assets must be fully directed to achieving social, religious, or humanitarian goals. However, in practice, the need for professionalism and high workloads often require Foundation administrators to receive reasonable compensation. This study aims to analyze the legal provisions regarding the provision of remuneration for Foundation administrators in Indonesia and to evaluate the dispute resolution mechanisms that may arise, by referring to Law No. 28 of 2004 concerning Amendments to Law No. 16 of 2001 concerning Foundations. This study uses a normative legal approach with a prescriptive analysis method, and finds that remuneration is permitted as long as the administrator is not a founder, patron, or supervisor; carries out his duties directly and fully; and is regulated transparently in the Articles of Association. In the event of a dispute, the resolution can be reached through deliberation, mediation, arbitration, or court. This study also highlights the importance of accountability, internal supervision, and regulatory intervention from the government in maintaining the integrity of Foundation governance. Thus, the law on foundations in Indonesia needs to be continuously strengthened to remain relevant to social dynamics and the practical needs of professional management of non-profit organizations. Remuneration for Foundation administrators is permitted on the condition that the administrators are not founders, advisors, or supervisors, carry out their duties directly and fully, and are regulated transparently in the Articles of Association. Dispute resolution can be carried out through deliberation, mediation, arbitration, or court, with an emphasis on accountability, internal supervision, and the need for government regulation to strengthen Foundation governance.